Diastolic Dysfunction in Asymptomatic Type 2 Diabetic Patients Having Preserved Systolic Function - Baloch, Mir Waqas; Zameer, Imran; Khan, Kashif; Majeed, Zoha; Asad, Muhammad; Asad, Muhammad; Abbass, Khurrum; Sana, Ayesha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine frequency of diastolic dysfunction in asymptomatic type 2 diabetic patients by employing twodimensional (2D) echocardiography as a measurement method. Study Design: It was an Analytical Cross sectional study. Place and Duration of Study: Rawalpindi Institute of Cardiology, Rawalpindi Pakistan, from Jul 2021 to Nov 2021 Methodology: Patients, already diagnosed as diabetics for more than 5 years and on dietary control or on medications,presenting to the outpatient department of the hospital were enrolled. They were subjected to a 2D echocardiography in left lateral position. We excluded patients with valvular heart disease, ischemia, congestive heart failure, cardiomyopathy of any aetiology, renal failure, pulmonary illness, anemia, hemoglobinopathies, prior myocardial infarctions in any region, smokers,and hypertension. Diastolic dysfunction was evaluated as per the guidelines of American society of Echocardiography. Results: Overall (n=150) patients were calculated with reference to 11% prevalence of LVDD by sample size calculator, being the part of study who were fulfilling the inclusion criteria. There were 102(68.0%) male and 48(32.0%) female patients; mean age was 45.02±6.07 years. Mean duration of diabetes mellitus in years was 6.93±2.53 with ranges from 5 to 16 years. Patients on oral hypoglycemic were 121(80.7%), on insulin were 5(3.3%), on dietary control were 12(8%) and on mixed treatment were 12(8%). There were 58 (38.7%) patients who had diastolic dysfunction present on echocardiogram. Effect modifiers of duration of diabetes (p=0.2) did not show significant association; however, Age (p=0.001) and Gender (p=0.038) significantly associated with Diastolic Dysfunction. Conclusions: One of the simple and noninvasive approaches to diagnose diastolic dysfunction is doing 2D echocardiography which can identify large percentage of diabetic subjects having pre-clinical diastolic dysfunction. Thus, by on time detection we can initiate treatment and retard the progression of diastolic dysfunction.